Karakterisasi Karbon Aktif Asal Tumbuhan dan Tulang Hewan Menggunakan FTIR dan Analisis Kemometrika - Yusraini Dian Inayati Siregar; Rudy Heryanto; Nur Lela; Tri Heny Lestari (Jurnal Kimia Valensi, 2015)
Activated carbon is widely used as an adsorbent in gas purification, refining pulp, and also for the purification of food products, among others, oil purification, refining cane sugar, beet sugar, corn sugar, eliminate the taste and odor of drinking water. Carbon active can be derived from plant and animal bone. This study aims to analyze the differences in spectral profile of activated carbon from plants and animal bones by using FTIR. The data combined with the results of FTIR analysis chemometrics to classify and categorize the data, so it is clear where the activated carbon from plants and animal bones. FTIR analysis methods combined with chemometrics analysis through modeling PCA (Principal Component Analysis) and PLS-DA (Partial Least Squares-Discriminant Analysis) is able to distinguish between activated carbon derived from plants (coconut shell) and animal bones (beef and pork). PCA with total diversity of 89% were able to classify the samples of activated carbon plant and animal bones. PLSDA models successfully predicted the test sample is based on a sample group of activated carbon raw material. Manufacture of activated carbon predictive models with PLS calibration generates R2, R2 predictions, RMSEC, and RMSEP respectively by 0.9787389, 0.9662152, 0.0687364 and 0.0928362. The results showed that FTIR spectra and can be used to distinguish chemometrics activated carbon derived from plant and animal bonesDOI :http://dx.doi.org/10.15408/jkv.v0i0.3146.